Optimal decisions of closed-loop supply chain under government recycling subsidy and value co-creation - Liao, Bifeng; Shang, Yuanchao; Sun, Yangyi (Frontiers in Energy Research, 2023)
Several countries and regions have adopted recycling subsidy policies to encourage recycling activities and enacted recycling laws to improve the recycling rate of waste electrical and electronic equipment (WEEE). These initiatives are designed to reduce the damage to the environment and natural resource consumption caused the enterprise. In this study, we analyze how government recycling regulations, value co-creation activities, and recycling subsidies influence the pricing and output decisions of members of a closed-loop supply chain. We develop a Stackelberg game model led by manufacturers and followed by retailers to explore the impact of value co-creation activities and recycling subsidies on the quantity of new and remanufactured products, recyclers’ prices and prices of recycled electronic parts, manufacturers’ capacity to recycle, and environmental performance in the context of government recycling regulations. Manufacturers can choose from three recycling modes: mandatory minimum remanufacturing (SDW model), non-mandatory partial remanufacturing (SDO model), and full remanufacturing (SDB model). The results show that 1) higher recycling subsidies optimize the recycling capacity of manufacturers, increasing the number of remanufactured products and reducing the market share of new products, which affects the price of new products. 2) higher recycling subsidies reduce the price of recycled electronic parts purchased by manufacturers, strengthen the bargaining power of consumers, increase the price of recyclers, promote the active participation of consumers in value co-creation activities, and increase the level of value co-creation. 3) higher recycling subsidies help to increase the economic value of all parties in the closed-loop supply chain (manufacturers, recyclers, consumers), but stricter recycling constraints are not always beneficial to environmental performance; environmental taxes and fees above a certain threshold of recycling constraints reduce the negative impact of production activities on the environment. The novelties and contributions of this research include proposing a new application for the Value Co-creation and Government policy utilized to Supply Chain and their impact on sustainable supply chain. In addition, we proposed three new recycling strategies and analysed the impact of environmental tax on the environmental performance. Therefore, this study aims to provide some insights for government policymakers and for managers when facing a more complex business environment.